Pengaruh Rasio Profitabilitas, Pertumbuhan Penjualan, dan Operating Cash Flow Terhadap Keputusan Investasi Saham: Studi Eksperimen Pada Calon Investor Pemula - Apriliani, Lina; Kesuma, Wendy (Keizai, 2025)
This study aims to analyze how profitability ratios, sales growth, and operating cash flow affect investment decisions empirically. The research employs an experimental methodology with a logistic regression approach. The sample consists of 50 novice investors who have acquired basic investment knowledge. The results indicate that profitability ratios, sales growth, and operating cash flow positively and significantly impact investors' stock investment decisions. Sales growth exhibits the strongest influence on investment decisions. These findings confirm that investors tend to make more rational investment decisions when they understand the fundamental aspects of a company.